The Concept of Mubᾱdalah (Mutuality) and the Public Role of Wife to Prevent Domestic Violence - Na’mah, Ulin; Qamaria, Rezki Suci; Makrufah, Hesti Ayu (Universitas Islam Negeri Raden Intan Lampung, 2022)
This research is motivated by an increase in data on complaints and acts of violence against women/housewives every year. For this reason, in this article, the author offers efforts to prevent domestic violence through a new perspective, namely Mubᾱdalah (mutuality). Mubᾱdalah is a concept formulated by Faqihuddin Abdul Kodir that can be applied in household life. In this study, the Mubᾱdalah concept is used as an effort to prevent domestic violence. This research is library research, which is research conducted using data sourced from the library. In this study, the author describes Faqihuddin Abdul Kodir's thoughts as the main basis for analyzing the public role of wives in preventing domestic violence. The conclusions obtained are: First, mubᾱdalah offers the concept of preventing domestic violence through three efforts, namely: instilling the mubadalah perspective on married couples, eliminating powerlessness or inequality in women, and changing the structure and culture in society. Second, the role of the wife in the public sphere is very important to prevent or minimize acts of violence in the household due to power relations or unequal relations between wives and husbands. Therefore, wives are encouraged not to depend on their husbands and to have a network of relationships that can become social support. in eliminating powerlessness and inequality of women in the public and domestic spheres.